2014
DOI: 10.1002/agr.21405
|View full text |Cite
|
Sign up to set email alerts
|

Do Brand Advertising Spillovers Matter?

Abstract: This article examines the spillover effects of television brand advertising on consumer demand, using carbonated soft drinks as a case study. Spillover effects are modeled using the conventional linear and constant elasticity of substitution (CES) advertising production functions. The latter allows for imperfect substitution between brand advertising and spillovers from advertising all other brands belonging to the same company as well as relaxes the assumption of constant returns to scale. Empirical results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…First, energy plays an important role in milk production as well as transportation and marketing (Brush et al., ). Second, given the prevalence of obesity and over‐consumption of sugar‐sweetened beverages (SSBs), milk is considered a lower‐calorie and more nutritious substitute for SSBs (Heard et al., ; Li and Lopez, ; Runge et al., ). Third, the price of milk as a staple food is closely connected with consumers’ welfare and social well‐being, particularly children's.…”
Section: Introductionmentioning
confidence: 99%
“…First, energy plays an important role in milk production as well as transportation and marketing (Brush et al., ). Second, given the prevalence of obesity and over‐consumption of sugar‐sweetened beverages (SSBs), milk is considered a lower‐calorie and more nutritious substitute for SSBs (Heard et al., ; Li and Lopez, ; Runge et al., ). Third, the price of milk as a staple food is closely connected with consumers’ welfare and social well‐being, particularly children's.…”
Section: Introductionmentioning
confidence: 99%
“…Generic advertising is the focus of many studies that evaluate the effect of advertising on demand for food and beverages. However, generic advertising does not distinguish products from different manufacturers, and it is impossible to evaluate the spillover effect of advertising among different brands (Li and Lopez 2015). Moreover, advertising can differ in numerous aspects such as geographical coverage or delivery methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This gap in the literature is particularly noteworthy as researchers have found that direct marketing channels for local foods (e.g., farm to consumer) have largely stagnated, with much of the growth in local food sales concentrated in intermediated marketing channels (Low et al, 2015). These intermediated marketing channels, including grocery stores, are well studied in other contexts (Cai et al, 2018; Jaenicke & Carlson, 2015; Li & Lopez, 2015) and differ from direct marketing channels in the large and varied nature of the processed and packaged goods offered to consumers.…”
Section: Introductionmentioning
confidence: 99%